Cone-beam differential phase-contrast laminography with x-ray tube source - Fu, J.; Biernath, T.; Willner, M.; Amberger, M.; Meiser, J.; Kunka, Danays; Mohr, J.; Herzen, Julia; Bech, Martin; Pfeiffer, F. (EPL - Europhysics Letters, 2014)
We report on an x-ray cone-beam differential phase-contrast computed laminography (DPC-CL) method for tomographic reconstruction of thin and lamellar objects. We describe the specific scan geometry of DPC-CL, which consists of a Talbot-Lau grating interferometer and a lab-based x-ray tube source, and derive a filtered back-projection (FBP) reconstruction algorithm. The experimental results of a flat sphere phantom and a piece of ham demonstrate the validity of the proposed technique. The existing DPC-CL methods are based on synchrotron sources and the parallel-beam geometry. In contrast, our approach adopts a more accessible x-ray tube source and a cone-beam geometry. Therefore it significantly widens the application range of phase-contrast laminography, particularly in practical laboratory settings, beyond applications at large-scale synchrotron facilities. © CopyrightEPLA, 2014.
CRIS-Team Scopus Importer:2023-03-08